MENTORING ACTIVE LEARNING CALISTUNG THROUGH DEMONSTRATION METHOD FOR ELEMENTARY SCHOOL CHILDREN - Indriyani, Dian; Rahmi, Elvi; Baharuddin, Wiska (jfpublisher, 2022)
Introduction.The biggest influence on the growth and development of students is an educator or teacher. The use of demonstration method is to make students become more active in teaching and learning process. There are several child-centered learning approaches including; 1) Montesori approach model; 2) Street bank approach model; 3) High Scope approach model; 4) Creative curriculum approach model; 5) Regio Emilia approach model. This community service aims as one of the calistung learning strategies in teaching and learning process, especially in West Papua for low-grade students that aims for students to learn optimally. Method.This research is descriptive qualitative and analyzed with the Miles, Huberman and Saldana approach using a validation technique (triangulation). Result&Analysis.The community service stated that the demonstration method could effectively make students become more active in the calistung teaching and learning process. Discussion.This demonstration method can be seen very significant increases learning outcomes for elementary students.